Kaedah Pengambilan Riwayat Sejarah Al-Sahabat: Satu Kajian Terhadap Tarikh Al-Tabari - Zainul Abidin, Mohd. Asri (Jurnal Usuluddin, 2001)
Al-Qur'an and al-Sunnah highly commended the conduct of the companions of the Prophet (p.b.u.h), while some of historical annals depicted them as having such character which is most unsuitable to the conduct accorded by al-Qur'an and al-Sunnah. This article is based on Tarikh al-Tabari which is a very important source of reference on Islamic historical annals. By using this text, the conflicting views are analysed.